Mushrooms & Truffles - Oliveira, Paulo (2021)
This chapter aimed to compile the scattered available information on fungal ecology, productivity and socioeconomics, summarizing the suitable techniques and tools for enhancing mushroom and truffle production within the context of the multifunctionality of European forest ecosystems.